The Veterinary Profession in Greece. Review of the Present and Prospects for the Future. II. Duties and Responsibilities - ΧΑΤΖΗΟΛΟΣ, ΒΑΣΙΛΕΙΟΣ Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The new duties and responsibilities of the vetevinary profession resulting from scientific, technological, and social progress are discussed. Among the subjects dealt with are: unification of the veterinarians under a distinct, independent, and self-governing organization; preservation of the prestige and dignity of the profession; conscientious performance of duties guided by high moral and genuinely patriotic motivation; elimination of illegal use of drugs; eradication of zoonosis; development of healthy and fixed genotype experimental animals; promotion of veterinary medicine for pets; orientation toward and participation in biomedical and biological research; organization of group therapy and preventive veterinary medicine; reduced cost of treatment, increased efficiency, and reasonable fees for services rendered. Furthermore, recognition of the various specializations is suggested. Particular emphasis is made of two areas of responsibility which should fall within the purview of the veterinarians but which the agronomists have arrogated to themselves: (a) development of productive live stock readily adaptable to the Greek environment in order to enhance the output of this vital nutritional source, and (b) utilization of artificial insemination in order to accelerate (a) above. Also pointed out is the significance of the improvement of public health and of veterinarian participation in ecological research. Finally, discussion is made of the interrelationships of veterinarians, agronomists, physicians, pharmacists, zoologists, and directors of societies for animal protection. Also discussed is the possibility of using technicians in the veterinary profession.